Evaluation of MgO as a promoter for the hydrogenation of CO2 to long-chain hydrocarbons over Fe-based catalysts - Ahmed, Sheraz; Irshad, Muhammad; Yoon, Wonjoong; Karanwal, Neha; Sugiarto, Junjung Rohmat; Khan, Muhammad Kashif; Kim, Soek Ki; Kim, Jaehoon (Applied Catalysis B: Environmental, 2023)
Thermocatalytic conversion of CO2 into liquid fuels and chemicals is a promising approach to mitigate global warming. Although, the CO2 conversion and long-chain hydrocarbon selectivity are highly dependent on the choice of metal-oxide promoter, but role of the promoter remains unclear. Herein, the role of MgO as a promoter for an Fe-based catalyst was investigated. Bimetallic Na-FeMgOx catalyst exhibited a high C5+ yield of 25.1% with a CO2 conversion of 49.1% at the early stage of the reaction. The presence of MgO facilitates the reduction of Fe oxides and formation of oxygen vacancies by transferring electrons to Fe-based phases. In addition, at the early stage of reaction, the decoration of the Mg oxide surface with nanosized χ-Fe5C2 enhances the C5+ yield. However, the progressive transformation of MgO to MgCO3 during CO2 conversion deactivates the Na-FeMgOx catalyst. A detailed deactivation mechanism is also discussed.
Keywords: Bimetallics; CO2 hydrogenation; Deactivation; Fe catalyst; Fe-based catalysts; Long chain hydrocarbons; Metal-oxide; Mg promotor; Promotor; ]+ catalyst; CO2 hydrogenation; Deactivation; Fe catalyst; Fischer–Tropsch synthesis; Mg promotor